2019
DOI: 10.3389/fphys.2019.00345
|View full text |Cite
|
Sign up to set email alerts
|

The Exocyst Component Sec3 Controls Egg Chamber Development Through Notch During Drosophila Oogenesis

Abstract: The exocyst complex plays multiple roles via tethering secretory or recycling vesicles to the plasma membrane. Previous studies have demonstrated that the exocyst contains eight components, which possibly have some redundant but distinct functions. It is therefore interesting to investigate the biological function of each component. Here, we found that Sec3, one component of exocyst complex, is involved in Drosophila egg chamber development. Loss of sec3 results in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…Although studies using gene-deficient mouse models have shown that the exocyst is important for embryo development ( Mizuno et al, 2015 ; Friedrich et al, 1997 ; Fogelgren et al, 2015 ; Dickinson et al, 2016 ), its tissue-specific functions in adults are largely unknown. In Drosophila models, the exocyst plays an important role in the formation of both female and male gametes ( Giansanti et al, 2015 ; Wan et al, 2019 ; Murthy and Schwarz, 2004 ; Mao et al, 2019 ). In mice, all exocyst subunits are expressed in male germ cells at each stage of differentiation ( Green et al, 2018 ), and although it is predicted that these subunits may be involved in mammalian spermatogenesis, the function of these subunits is completely unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Although studies using gene-deficient mouse models have shown that the exocyst is important for embryo development ( Mizuno et al, 2015 ; Friedrich et al, 1997 ; Fogelgren et al, 2015 ; Dickinson et al, 2016 ), its tissue-specific functions in adults are largely unknown. In Drosophila models, the exocyst plays an important role in the formation of both female and male gametes ( Giansanti et al, 2015 ; Wan et al, 2019 ; Murthy and Schwarz, 2004 ; Mao et al, 2019 ). In mice, all exocyst subunits are expressed in male germ cells at each stage of differentiation ( Green et al, 2018 ), and although it is predicted that these subunits may be involved in mammalian spermatogenesis, the function of these subunits is completely unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Remarkably, however, mutations in some subunits are tolerated. Budding yeast can survive LoF mutations of EXOC1 ( Finger and Novick, 1997 ; Novick et al, 1980 ), for example, and in Drosophila, a truncation mutant of EXOC2 that retains the CorEx motif allows organismal viability ( Sommer et al, 2005 ; Wan et al, 2019 ). Exocyst function is also important for proper delivery to the primary cilium of the Joubert syndrome protein Arl13b and for ciliogenesis in a wide range of cell and tissue types.…”
Section: Introductionmentioning
confidence: 99%